REMEDIASI MISKONSEPSI RANGKAIAN LISTRIK DC MENGGUNAKAN MODEL POE BERBANTUAN PHET DAN ALAT PERAGA DI SMA - Riko, Marselius; Sitompul, Stepanus Sahala; Arsyid, Syaiful B (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to know the difference between the effectiveness of using to POE models assisted PhET simulaton and Props in reduction the quantity of students that misconception about electric circuit DC at SMA Santo Fransiskus Asisi Pontianak. This study design is quasi experimental design with nonequivalent control group design. The sample 23 students of experiment class I and 39 students of experiment class II. This partisipants were chosen by Purposive Sampling. Diagnostic test like multiple choices without reasons amount 8 questionts using to measure of student’s misconception. The results showed reduction percentage of students who misconceptions about 65,8% in experiment class I and 53,5% in experiment class II. Based on the Z of Proportion two test, there was the significant difference of the number of student’s misconception between the class remediated using POE models assisted PhET simulaton and the class remediated using POE models assested Props (Zhitung = -3,79, α = 5% dan -Ztabel -1.96). Remediation effectiveness showed by DQM value about 76% in experiment class I and 60% in experiment class II. This research is hoped can be the alternative to remediation of student’s misconceptions about the another subject of knowlegde in physics.Keywords:   Remediasi, POE, PhET, alat peraga.